(untitled) (International Journal Online of Humanities, 2020)
This paper aims at investigating technical English taught in Sudan higher education to find out whether the ESP meets the students’ needs when they join vocations and workplace. Twenty five students majored in different specializations participated in the study. They are graduates of different Sudanese Universities and Colleges. To yield more insights and more description, the following are the questions of the study: • How does English for Specific Purpose (ESP) courses meet students’ needs in their studies at colleges? • 2. Do ESP courses prepare students to the workplace? The results indicate that the majority of the participants were not satisfied with their courses they learned at colleges when they were students because those courses did not meet their needs in workplaces.